Penyelesaian Sengketa Wanprestasi terhadap Perjanjian Waralaba oleh Franchise kepada Franchisor pada Putusan Nomor 612/Pdt.g/2017/Jkt. Sel - Refalia, Salsa; Urbanisasi, Urbanisasi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this research is to analyze the resolution of default disputes in franchise agreements through a case study of Decision No. 612/Pdt.g/2017/Jkt. Considering that breach of contract is possible in any legal agreement, this research aims to examine the available remedies that can be taken. This study utilizes qualitative research based on written law as its primary source, namely the Indonesian Civil Code (KUHPerdata), Franchise Agreements, and License Agreements dated April 25 and June 18, 2015, as the validity of agreements is equated with the law for the parties involved. The default dispute in question began when the Defendant failed to pay royalty fees for the MySalon Jababeka and MySalon Galaxi Bekasi franchises from June 2016 to September 2017, resulting in losses for the Plaintiff. Various measures can be taken to resolve default disputes, including issuing warnings, holding negotiations, and resorting to litigation if no agreement is reached. However, due to the Plaintiff's continuous evasion and lack of good faith to fulfill their obligations, the Plaintiff eventually filed a lawsuit with the South Jakarta District Court on September 12, 2017. The panel of judges ruled that the Defendant was in default and obliged to compensate the Plaintiff for the incurred material losses.